Optimalisasi Dimensi Tabung Roasting Kopi Kapasitas 2 kg dengan Pendekatan Model Elemen Hingga - Dedi Suryadi; Bowo Anugrah; Ahmad Fauzan Suryono; Agus Suandi; Novalio Daratha (Department of Mechanical Engineering, Universitas Andalas, 2022)
Coffee roasting is an important process in the coffee industry that determines the quality of the coffee beverage obtained. The roasting process is carried out in a cylindrical tube having high temperature. Therefore, thermal stress on the cylindrical tube (drum) should be focused. In this paper, both appropriate materials selection and optimal dimension of the roaster drum are considered. Drum is given both thermal load of 200oC and a coffee load of 2 kg. Here, Aluminum Alloy 5083 and Stainless Steel 304 are analyzed as drum materials because these materials are recommended for foods. Finite element method is used for drum analysis with axisymmetric model. Moreover, optimal dimension of drum can be obtained by varying the length, diameter and thickness. The results show that Stainless Steel 304 is suitable material for drum under both thermal load and both thermal load of 200oC and a coffee load of 2 kg. While, dimensions of drum are length of 450 mm and diameter of 180 mm with thickness of drum larger than 1 mm.